2007
DOI: 10.1073/pnas.0610849104
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of subterritories of the subthalamic nucleus reveals its role in the integration of the emotional and motor aspects of behavior

Abstract: Two parkinsonian patients who experienced transient hypomanic states when the subthalamic nucleus (STN) was stimulated during postoperative adjustment of the electrical parameters for antiparkinsonian therapy agreed to have the mood disorder reproduced, in conjunction with motor, cognitive, and behavioral evaluations and concomitant functional neuroimaging. During the experiment, STN stimulation again induced a hypomanic state concomitant with activation of cortical and thalamic regions known to process limbic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
341
1
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 410 publications
(383 citation statements)
references
References 73 publications
27
341
1
14
Order By: Relevance
“…Therefore, we speculate that the absence of error-monitoring cells in PD might be related to a lower sampling of the STN subregions where these cells might be clustered. This idea would support a tripartite model of STN functional subterritories, in coherence with previous neuroimaging (Haynes & Haber, 2013;Karachi et al, 2005;Parent, 1990) and stimulation studies Lambert et al, 2011;Mallet et al, 2007;Sudhyadhom et al, 2007).…”
Section: 2supporting
confidence: 87%
“…Therefore, we speculate that the absence of error-monitoring cells in PD might be related to a lower sampling of the STN subregions where these cells might be clustered. This idea would support a tripartite model of STN functional subterritories, in coherence with previous neuroimaging (Haynes & Haber, 2013;Karachi et al, 2005;Parent, 1990) and stimulation studies Lambert et al, 2011;Mallet et al, 2007;Sudhyadhom et al, 2007).…”
Section: 2supporting
confidence: 87%
“…Case reports of PD patients with reversible changes in behaviour related to an acute increase in stimulation parameters comprise mirthful laughter [50], pathological crying [51], mania [25,52,53], aggressive behaviour [54] and acute dysphoria or depression [55,56]. Furthermore, STN DBS can contribute to certain impulsive behaviours during high-conflict decisions [57].…”
Section: The Stn and Impulsivitymentioning
confidence: 99%
“…Recently it has been shown that severe refractory OCD symptoms can be improved by high frequency stimulation of the subthalamic nucleus (STN) (Chabardè s et al, 2012;Fontaine et al, 2004;Mallet et al, 2008). The STN is a key * Corresponding author.…”
Section: Research In How the Brain Processes Information Is Importantmentioning
confidence: 99%
“…Recently it has been shown that severe refractory OCD symptoms can be improved by high frequency stimulation of the subthalamic nucleus (STN) (Chabardè s et al, 2012;Fontaine et al, 2004;Mallet et al, 2008). The STN is a key structure of basal ganglia connecting motor, limbic and associative systems, because it is known from Parkinson's disease (PD) patients that deep brain stimulation (DBS) of the STN can have significant effects on mood and cognition, including mirthful laughter (Krack et al, 2001), acute depression (Bejjani et al, 1999), aggressiveness (Bejjani et al, 2002), hypomania or full blown mania (Krack et al, 2001;Mallet et al, 2007;Ulla et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation